2010
DOI: 10.1111/j.1462-5822.2009.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

EspM2 is a RhoA guanine nucleotide exchange factor

Abstract: We investigated how the type III secretion system WxxxE effectors EspM2 of enterohaemorrhagic Escherichia coli, which triggers stress fibre formation, and SifA of Salmonella enterica serovar Typhimurium, which is involved in intracellular survival, modulate Rho GTPases. We identified a direct interaction between EspM2 or SifA and nucleotide-free RhoA. Nuclear Magnetic Resonance Spectroscopy revealed that EspM2 has a similar fold to SifA and the guanine nucleotide exchange factor (GEF) effector SopE. EspM2 indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Moreover, although not similar in sequence, the chemical properties of the residues within the putative catalytic loop of SifA are comparable to those found in SopE (51). Nonetheless, despite its similarities with SopE and the ability to bind RhoA, no GEF activity has yet been demonstrated for SifA (4,51).…”
Section: Wxxxe Effectors: From Rho Gtpase Mimics To Rho Gtpase Gefsmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, although not similar in sequence, the chemical properties of the residues within the putative catalytic loop of SifA are comparable to those found in SopE (51). Nonetheless, despite its similarities with SopE and the ability to bind RhoA, no GEF activity has yet been demonstrated for SifA (4,51).…”
Section: Wxxxe Effectors: From Rho Gtpase Mimics To Rho Gtpase Gefsmentioning
confidence: 80%
“…Two recent independent reports have shown that several WxxxE effectors are also Rho GTPase GEFs (4,36). First, Huang et al demonstrated that Map specifically binds nucleotide-free Cdc42 and is able to induce the release of GDP and the incorporation of GTP (36).…”
Section: Wxxxe Effectors: From Rho Gtpase Mimics To Rho Gtpase Gefsmentioning
confidence: 99%
“…In addition, SifA can bind to RhoA in human HeLa cells [212], and an interaction of SifA with a Rho GTPase has also been found using the model organism Saccharomyces cerevisiae [216]. However, the ability of SifA to catalyze nucleotide exchange on RhoA has not been demonstrated [217]. Interestingly, SKIP also interacts, through its PH domain, with the late endosome GTPase Rab9.…”
Section: 5mentioning
confidence: 99%
“…Rho GTPases are targeted by many bacterial effector proteins, including Yersinia pseudotuberculosis YopE (30), Salmonella enterica serovar Typhimurium SopE (40), Vibrio cholerae RTX toxin (41), and Escherichia coli EspH (29), indicating this is a conserved target of bacterial pathogens (42). Bacterial virulence factors and toxins regulate Rho activity using at least one of three methods (42): (i) through indirect regulation of localization and activation by mimicking Rho GAPs, guanine nucleotide exchange factors (GEFs), or guanine nucleotide dissociation inhibitors (GDIs) (30,43); (ii) direct regulation through posttranslational modifications, including ADP-ribosylation (44), adenylation (45), deamidation (46), and glucosylation (47); (iii) or through targeting upstream regulators (29,48). Consequently these modifications affect Rho GTPase activity and ultimately impact host signaling pathways, resulting in inhibition of immune function or endocytosis, generating a more permissive host for the pathogen.…”
Section: Discussionmentioning
confidence: 99%